Guidelines for the peri‐operative care of people with dementia: Guidelines from the Association of Anaesthetists. (11th January 2019) - White, S.; Griffiths, R.; Baxter, M.; Beanland, T.; Cross, J.; Dhesi, J.; Docherty, A. B.; Foo, I.; Jolly, G.; Jones, J.; Moppett, I. K.; Plunkett, E.; et al.
Summary: Ageing populations have greater incidences of dementia. People with dementia present for emergency and, increasingly, elective surgery, but are poorly served by the lack of available guidance on their peri‐operative management, particularly relating to pharmacological, medico‐legal, environmental and attitudinal considerations. These guidelines seek to deliver such guidance, by providing information for peri‐operative care providers about dementia pathophysiology, specific difficulties anaesthetising patients with dementia, medication interactions, organisational and medico‐legal factors, pre‐, intra‐ and postoperative care considerations, training, sources of further information and care quality improvement tools. 개요: 노령 인구는 더 높은 치매(dementia)의 유병률을 가지고 있다. 치매 환자들은 응급 수술을 포함하여 점점 더 많은 수 술을 받고 있지만, 그들의 주술기 관리, 특히 약리학적, 의료법 학적(medico‐legal), 환경적 및 태도적(attitudinal) 고려사항 과 관련하여 이용 가능한 지침이 부족하여 제대로 수행되지 못하고 있다. 본 가이드라인을 통하여 치매의 병태생리, 치매 환자의 마취에서의 특수한 어려움, 약물 상호 작용, 조직적 (organisational) 및 의료법학적 요소, 수술 전/중/후 진료에 서의 고려사항, 수련(training), 추가 정보의 출처 및 의료 품 질 개선 도구 등에 대한 정보를 주술기 의료 제공자에게 제공 함으로써 치매 환자의 주술기 관리를 성공적으로 수행하는 데 도움이 되는 지침을 전달하고자 한다.